Expanding Students’ Choices in Language Education - Jacobs, George; Renandya, Willy (Journal of Modern Languages, 2021)
Many teachers seem interested in their classes being more student-centered. Students making more choices about their own learning forms a key aspect of student-centered learning, as well as life-long learning. This article offers ideas for ways to provide students with more choices in their learning and suggests ways to encourage students to make choices when given opportunities to do so. These ideas for increasing student choice include extensive reading, cooperative learning, multiple intelligences, service learning, thinking questions, and use of the internet and other IT affordances. Student choice fits with an overall paradigm shift toward democratizing society, and it also fits with greater choice for teachers. Theoretical underpinnings of student choice include social cognitivism, social constructivism, humanistic psychology, self-directed learning, and social interdependence theory.